Dynamic changes in the aroma profile of Qingzhuan tea during its manufacture. (1st May 2022) - Liu, Panpan; Zheng, Pengcheng; Feng, Lin; Gong, Ziming; Zheng, Lin; Gao, Shiwei; Wang, Xueping; Ye, Fei; Huang, Jianan; Liu, Zhonghua
Graphical abstract: Highlights: Changes in characteristic aroma-active compounds occur during processing at an industrial scale. Pile fermentation increases the proportion of olefinic aldehyde compounds. Methoxybenzene compounds formed during pile fermentation were weakened by aging. Olefinic aldehydes, ketones, and methoxybenzenes were the characteristic volatiles of aged fragrances. Abstract: Changes in key odorants and aroma profiles of Qingzhuan tea (QZT) during its manufacture were determined using headspace solid-phase microextraction gas chromatography-mass spectrometry/olfactometry. An aroma profile was constructed to illustrate sensory changes during manufacture. The characteristic aroma of QZT was aged fragrance, which was mostly developed during pile fermentation and was enhanced during the aging and drying stages. Using volatile compounds found in the raw materials, sun-dried green tea and QZT finished product were compared by orthogonal partial least square-discriminant analysis. Among 108 detected volatiles, 19 were significantly upregulated and 15 were downregulated. ( E )-β-Ionone, ( E, Z )-2, 6-nonadienal, 1-octen-3-one, ( E, E )-2, 4-heptadienal, ( E, E )-2, 4-nonadienal, safranal, ( E )-2-nonenal, α-ionone, and 1, 2, 3-trimethoxybenzene were found to be significant contributors to the aged QZT fragrance, reflecting their high odor-activity values and aroma intensities. Finally, the metabolic transformation of key aroma-active compounds was systematically analyzed. This study provided a theoretical basis for improving the processing and quality of QZT.